TARKAM: The Advanced Robotic Kicker and Automation Machine for Goalkeeper Training - Hendi Purnata; Supriyono; Sugeng Dwi Riyanto; Dwi Aji Nugroho; Wahidun Sholih (Journal of Innovation Information Technology and Application)
This research aims to design and implement a ball-throwing robot that is used to train goalkeeper skills, such as reflexes and the ability to read the direction of the ball. The main focus of the research is to develop a ball throwing system that can provide a variety of shots with high precision, as well as overcome the limitations of manual training that relies on the individual skills of the kicker. This ball-throwing robot is controlled through a smartphone using a Bluetooth HC-05 module as a means of communication, and is equipped with two DC spindle motors, two DC PG36 motors, and two DC 12V motors to regulate the direction and speed of the ball. The ball direction and rotation control uses PID (Proportional-Integral-Derivative) control to ensure stable and accurate ball launching. The system dynamically adjusts the ball speed and direction based on position and angle sensor feedback. Tests were conducted at three different distances, namely 5 meters (100% accuracy), 7 meters (100% accuracy), and 11 meters (80% accuracy). The test results show that this ball-throwing robot is able to deliver shots with high precision, move flexibly and quickly, and adjust the direction and speed of the ball effectively. The results of the ANOVA test (p < 0.005) showed a statistically significant difference in average firing accuracy at all three distances. This research makes a practical contribution to improving the effectiveness of goalkeeper training, as well as offering a more efficient solution in football training. This research makes a practical contribution in improving the effectiveness of goalkeeper training, as well as offering a more efficient solution in soccer training.